Influence of cold atmospheric pressure plasma treatment on germination and plant biomass of Trifolium pratense L. - Mareike Kavka; Henrike Brust; Christine Brandt; Thalita M. C. Nishime; Evelin Willner; Nicola Wannicke; Klaus J. Dehmer (PLoS ONE, 2025)
Treatment of seeds with cold atmospheric pressure plasma (CAPP) is in its proof-of-concept phase with regard to its effect on germination and plant growth. To increase the germination of hardseeded red clover (Trifolium pratense L.), seeds are usually scarified, which is time-consuming and labour-intensive. The aim of this study was to compare the effect of different CAPP devices (indirect treatment: plasma processed air, direct treatment: corona discharge, argon and air dielectric barrier discharge) on germination and early growth of different long-term stored red clover accessions and to determine whether germination can be increased to meet seed management requirements. Sixty different red clover seed lots (diverse accessions and harvest years) with different initial germination percentages were divided into three batches of 20 lots each and the effect of the different plasma treatments on germination and development were examined in laboratory and greenhouse. The overall results indicate a plasma discharge- and accession-depended enhancement of germination speed which was detected in all batches but most pronounced in Batch 1. While direct treatments, especially with corona discharge-plasma, increased germination speed (up to 58% germination seven days after sowing vs. 44% in control in laboratory conditions), treatment with plasma processed air resulted partially in reduced germination speed (42%). Despite a small but significant increase in total germination of maximum five percentage points, no treatment led to an increase from 62% or 70% in control (depending on experiment) to at least 80% germination percentage to meet storage requirements for seed banks. Stimulating effects on biomass of young plants under greenhouse cultivation conditions were observed in Batch 1, but were absent in Batch 2 and 3 and therefore inconclusive. Future research is needed to elucidate influencing factors on plasma effects in red clover seed lots which include but are not limited to the effect of seed coat compounds and seed coat thickness.